PENGAWASAN PENERAPAN UPAH MINIMUM KOTA (UMK) DI KOTA BATAM - Angga Ilham Pratama; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Wage workers in Batam does not meet all our expectations, not supervised by the related parties. In fact many workers or workers who are not granted in accordance with the wage set by the government. Companies that violate not get strict sanctions. This phenomenon can not be allowed to continue because the wage is sought by the worker to resume his life. Not just wages but decent wages for life to workers or laborers.In theory oversight by Manullang, who says there are three indicators of supervision is setting standards, conducting judging, and perform corrective action. This study aims to determine supervision of the implementation of minimum wages cities (UMK) in the city of Batam.The research model used in this research is descriptive qualitative research. With Accidental sampling technique used, the key informant that the Department of Labor study of Batam.Based on the research that has been done, by referring to the concept of the theory that surveillance in Batam city is not optimal by the Department of Labor Batam.Terdapat some shortcomings such as in setting standards, malakukan assessment measures and corrective actions have not run with the maximum. It is caused by factors that can include lack of supervision supervisory personnel, a lack of understanding of employers and workers on the applicable rules, facilities and infrastructure and the lack of worker complaints.Keywords: Monitoring, Application of State Minimum Wage (UMK)